Minimizing the Entropy Penalty for Ligand Binding: Lessons from the Molecular Recognition of the Histo Blood‐Group Antigens by Human Galectin‐3. Issue 22 (17th April 2019) - Gimeno, Ana; Delgado, Sandra; Valverde, Pablo; Bertuzzi, Sara; Berbís, Manuel Alvaro; Echavarren, Javier; Lacetera, Alessandra; Martín‐Santamaría, Sonsoles; Surolia, Avadhesha; Cañada, Francisco Javier; Jiménez‐Barbero, Jesus; Ardá, Ana
Abstract: Ligand conformational entropy plays an important role in carbohydrate recognition events. Glycans are characterized by intrinsic flexibility around the glycosidic linkages, thus in most cases, loss of conformational entropy of the sugar upon complex formation strongly affects the entropy of the binding process. By employing a multidisciplinary approach combining structural, conformational, binding energy, and kinetic information, we investigated the role of conformational entropy in the recognition of the histo blood‐group antigens A and B by human galectin‐3, a lectin of biomedical interest. We show that these rigid natural antigens are pre‐organized ligands for hGal‐3, and that restriction of the conformational flexibility by the branched fucose (Fuc) residue modulates the thermodynamics and kinetics of the binding process. These results highlight the importance of glycan flexibility and provide inspiration for the design of high‐affinity ligands as antagonists for lectins. Abstract : Conformational preorganization of the natural A/B blood‐group antigens is the origin of the high‐affinity interaction with human galectin‐3, a lectin of increasing biomedical interest. A combination of structural techniques shows that the fucose residue does not participates in direct contacts with the protein, however it modulates the kinetics and thermodynamics of the molecular recognition process.